The Comparison of Dijsktra’s Algorithm and Flyod Warshall’s Algorithm to Determine The Shortest Path of Traditional Markets in Bandar Lampung City - Poetri Hana Nurhandayani; Wamiliana Wamiliana; Misgiyati Misgiyati; Notiragayu Notiragayu; Muslim Ansori (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2024)
Determining the shortest path between one location to another location is one of the problems that usually has to be faced in daily life. The shortest path will affect the shorter time needed, less money used, and others. In this study, we will discuss the comparison of Dijsktra’s Algorithm and Floyd Warshal’s Algorithm to determine the shortest path of the biggest and the most famous traditional market in Bandar Lampung City, which is Bambu Kuning traditional market, to 26 other traditional markets in Bandar Lampung city. The Phyton programming language is used to implement both algorithms on the data of 27 traditional markets. The results show that both algorithms give the same solution. However, the processing time of Dijsktra’s Algorithm (0.1063 seconds) is faster than Floyd Warshal’s algorithm (0.1691 seconds)